2009 IEEE Electrical Insulation Conference 2009
DOI: 10.1109/eic.2009.5166374
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on dielectric properties of enameled wires with nanofilled varnish for rotating machines fed by inverters

Abstract: The dielectric and mechanical properties of standard (PEI), nanoscale-filled and microscale-filled varnishes are detailed and analyzed in this communication. Fumed silica (10nm and 400nm) have been tested as a filler. A particular attention has been paid to Partial Discharge Inception Voltage, Lifetime under pulse voltage and bonding strength which are crucial for varnish to be used in rotating machines fed by inverters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…The authors of this paper propose to add nano or micro silica not to the enamel but to the impregnating resin, because it is also the important part of DIS. The increased in lifetime under pulse voltage by using such silica fillers in varnish was shown recently [5]. This paper presents a comparative study of a Polyetherimide resin with or without fillers.…”
Section: Introductionmentioning
confidence: 97%
“…The authors of this paper propose to add nano or micro silica not to the enamel but to the impregnating resin, because it is also the important part of DIS. The increased in lifetime under pulse voltage by using such silica fillers in varnish was shown recently [5]. This paper presents a comparative study of a Polyetherimide resin with or without fillers.…”
Section: Introductionmentioning
confidence: 97%
“…In dielectrics all the electrons are bound to their parent molecules and there were no free charges [2]. The dielectrics are non metallic materials with high specific resistance and have negative temperature coefficient of resistance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the use of nano composites in the matrix of polymeric materials can greatly improve the thermal, mechanical and electrical properties of polymeric nano composites [4]. In the last few years, a great deal of attention has been given to the application of nano dielectrics in the field of electrical materials.…”
Section: Introductionmentioning
confidence: 99%